Dampak Sustainability Reporting dan Determinan Audit Delay - Silvi Malvina Oktaviani; Dwi Prastowo Darminto; Syahril Djaddang (Owner : Riset dan Jurnal Akuntansi, 2023)
The financial statements of companies going public must be reported annually. Based on the regulation of the Financial Services Authority (OJK) Number 29/POJK.04/2016 states that companies or issuers are required to report their annual reports to the Financial Services Authority no later than the end of the fourth month after the end of the financial year (120 days), Timely submission of financial reports done by the company will be subject to sanctions. This study aims to determine the effect of profitability, solvency, and company size on audit delay. The population in this study are LQ45 companies listed on the IDX (Indonesian Stock Exchange) for the period 2017-2021. There are 45 public companies listed on the Indonesian Stock Exchange, which are registered as a population. The selected sample uses a purposive sampling technique, and a sample of 64 is obtained. This research model uses panel data regression using E-views version 12. The results of this study indicate that profitability has no effect on audit delay, solvency has an effect on audit delay, firm size effect on audit delay, sustainability reporting is not able to moderate the effect of profitability on audit delay, and sustainability reporting is able to moderate the effect of solvency on audit delay. Subsequent research can add to research in other sectors such as manufacturing, mining and real estate.